2021
DOI: 10.3390/cancers14010171
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Based on Dendritic Cells Electroporated with an Exogenous Ovalbumin Protein and Pulsed with Invariant Natural Killer T Cell Ligands Effectively Induces Antigen-Specific Antitumor Immunity

Abstract: (1) Background: Cancer vaccines are administered to induce cytotoxic CD8+ T cells (CTLs) specific for tumor antigens. Invariant natural killer T (iNKT) cells, the specific T cells activated by α-galactosylceramide (α-GalCer), play important roles in this process as they are involved in both innate and adaptive immunity. We developed a new cancer vaccine strategy in which dendritic cells (DCs) were loaded with an exogenous ovalbumin (OVA) protein by electroporation (EP) and pulsed with α-GalCer. (2) Methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In addition, the mixture of EL4 lysate with VP-R8 did not affect cell viability after pulsation. Electroporation is one of the efficient methods to transduce proteins into dendritic cells to induce dendritic cell-based vaccines, but preserving cell viability after transduction is challenging [ 22 ]. Our results suggested that VP-R8 is a safer and more efficient modality to deliver tumor antigens into dendritic cells than conventional electroporation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mixture of EL4 lysate with VP-R8 did not affect cell viability after pulsation. Electroporation is one of the efficient methods to transduce proteins into dendritic cells to induce dendritic cell-based vaccines, but preserving cell viability after transduction is challenging [ 22 ]. Our results suggested that VP-R8 is a safer and more efficient modality to deliver tumor antigens into dendritic cells than conventional electroporation.…”
Section: Discussionmentioning
confidence: 99%